Novel coronavirus – SARS CoV-2 - Polz-Dacewicz, Małgorzata (Polish Journal of Public Health, 2020)
Coronaviruses cause a variety of diseases in mammals and birds. In late December, 2019, patients presenting with viral pneumonia due to an unidentified microbial agent were reported in Wuhan, China. A novel coronavirus was subsequently identified as the causative pathogen, provisionally named 2019 novel coronavirus (2019-nCoV). This virus appears to be a new human pathogen. In this article the biology of virus has been described, replication cycle and epidemiology of COVID 19. The next part discusses current methods of laboratory diagnostics. The coronavirus disease 2019 (COVID-19) pandemic has focused attention on the need to develop effective therapies against the causative agent, SARS-CoV-2. Researchers are therefore focusing on steps in the CoV replication cycle that may be target to inhibition by broad-spectrum or specific antiviral agents. Many laboratories focus on vaccine development. SARS-CoV-2 vaccines will be essential to reduce morbidity and mortality if the virus establishes itself in the human population. Novel coronavirus – SARS CoV-2